Multifactorial and multiple component interventions for preventing falls in older people living in the community - Hopewell, S; Adedire, O; Copsey, B; Sherrington, C; Clemson, L; Close, J; Lamb, S (Wiley: Cochrane Collaboration, 2016)
This is the protocol for a review and there is no abstract. The objectives are as follows: To assess the effects (benefits and harms) of multifactorial interventions and multiple component interventions for preventing falls in older people living in the community.